Pengaruh Profitabilitas, Thin Capitalization dan Transfer Pricing terhadap Agresivitas Pajak - Nanda Lestari; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This study was conducted to investigates the influence of profitability, thin capitalization and transfer pricing on tax aggressiveness in non-financial multinational companies listing on (BEI) the Indonesia Stock Exchange in 2019-2021. Population was determined using purposive sampling, 36 companies were selected. Data was processed using SPSS 26 with multiple linear regression analysis method. The findings prove that profitability and transfer pricing have no influence on tax aggressiveness, while thin capitalization has a significant influence on tax aggressiveness.